Advances in biological and chemical terrorism countermeasures - Kendall, Ronald J.; Presley, Steven M.; Austin, Galen P.; Smith, Philip N. (CRC Press, 2008)
Based on the findings of a multidisciplinary toxicology research program, this book explores improved methods of implementing countermeasures to biological and chemical terrorism. It focuses on modeling, simulation, and visualization; environmental protection; personal protection and therapeutics; and, the mechanistic and toxic effects of weapons.